2016
DOI: 10.4338/aci-2015-11-soa-0157
|View full text |Cite
|
Sign up to set email alerts
|

Using Telehealth to Reduce All-Cause 30-Day Hospital Readmissions among Heart Failure Patients Receiving Skilled Home Health Services

Abstract: Telehealth was associated with a reduction in all-cause 30-day readmission for one mid-sized Medicare-certified home health agency. A description of the program is presented as well as lessons learned that have significantly contributed to this program's success. Future expansion of the program is planned. Telehealth is a promising approach to caring for a chronically ill population while improving a patient's ability for self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 16 publications
3
59
1
Order By: Relevance
“…If independently validated in other studies, these risk profiles could be used by primary care and other community-based clinicians to identify older adults living in the community who may be at risk for poor outcomes and trigger clinicians to initiate individualized, targeted interventions. Targeted interventions may include the initiation, continuation or increased frequency of several community-based services such as nurse-led care coordination, 34 home health care, 39,40 hospice, phone calls between visits, 41 telehealth, 42 physician follow up 43 and handyman services 44 to mitigate risk. Additionally, the risk profiles, if further refined, could be integrated into clinical decision support systems to assist clinicians identify specific community-based referrals needed by older adults according to their level of risk.…”
Section: Discussionmentioning
confidence: 99%
“…If independently validated in other studies, these risk profiles could be used by primary care and other community-based clinicians to identify older adults living in the community who may be at risk for poor outcomes and trigger clinicians to initiate individualized, targeted interventions. Targeted interventions may include the initiation, continuation or increased frequency of several community-based services such as nurse-led care coordination, 34 home health care, 39,40 hospice, phone calls between visits, 41 telehealth, 42 physician follow up 43 and handyman services 44 to mitigate risk. Additionally, the risk profiles, if further refined, could be integrated into clinical decision support systems to assist clinicians identify specific community-based referrals needed by older adults according to their level of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 15 quantitative non-randomized studies, 13 met all quality appraisal criteria, one showed a rate of complete outcome data of <80% [17], and another lacked inclusion and exclusion criteria for participant selection [18]. Of the two quantitative descriptive studies, one satisfied all criteria [19] and the other lacked criteria for the risk of non-response bias; moreover, the authors did not balance for any potential confounding factors such as patient age, level of education, or duration of HF [20].…”
Section: Data Evaluationmentioning
confidence: 99%
“…In total, 17 of the 25 studies were conducted in North America [17-22, 24-27,29,31,34,37-40], three in Europe [23,30,35], three in China [16,28,32], and two in Iran [33,36]. Thirteen of the 25 studies did not report racial ethnicity [16,20,21,23,24,26,28,30,32,33,35,36,38]. The sample size ranged from 38 [24] to 3462 [19], and the average patient age was between 65 [36] and 82 years [27,30].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations